A Multi-polarized Antenna System for Combating Multipath Fading in UHF/RFID Frequency Band in Moving Vehicles - Deock Ho Ha; Je-Sung Ahn; Yeon-Wook Choe (2010 International Conference on Communications and Mobile Computing, 2010)
This paper proposes a multi-polarized antenna system with UHF/RFID frequency band for combating multi-path fading in short-range radio propagation environments. The multi-polarized antenna system of the UHF/RFID for using moving vehicles is composed of multiple micro-strip antenna combinations connecting by the RF combiner and diversity unit. From the measurement results it can be seen that the multipath fading occurred in LOS (line-of-sight)/NLOS(non-line-of-sight) short-range radio wave propagation environment is markedly reduced by using the proposed multi-polarized antenna system.